Collection development policies and practices in medical school rare book libraries. - Overmier, J (1984)
A survey of collection development policies and practices in medical school rare book libraries indicated that only 20% had documented criteria for collection development. The advantages of preparing and maintaining a formal written collection development policy are presented with guidelines for formulating such a policy.